The Relationship Between Students Interests and Attitudes: A Study of Junior High School in Batanghari City - Retni Sulistiyoning Budiarti; Dwi Agus Kurniawan; Rido Ilham Widodo; Wahyu Adi Pratama (AL-ISHLAH: Jurnal Pendidikan, 2022)
The urgency of this research is that it is expected to be a reference for teachers to find out the interests and attitudes of students at the state junior high school or madrasah tsanawiyah level on the respiratory system material. This study aims to determine how the relationship between interests and attitudes of students at a state junior high school  and a state madrasah tsanawiyah in Batanghari on the respiratory system material. The instrument used was a questionnaire which was distributed to students using descriptive quantitative methods. The data analysis technique used is descriptive statistics and inferential statistics, using normality, homogeneity, and regression tests. In the study, it was found that there was a significant relationship between the variables of interest in learning and the attitudes of students in learning the respiratory system material for both students. This is indicated by the table of regression test results, which shows that the B value is positive, other evidence is also shown from the t-count value which is larger and has a positive value compared to the t-table value which indicates the interest variable has a relationship with the attitude variable. Therefore, it is very important to develop students' interest in the respiratory system material in order to improve students' learning attitudes, so that it can help improve their learning outcomes.